PARENTS' INVOLVEMENT AND ACADEMIC PERFORMANCE OF PRIMARY SCHOOL PUPILS IN LIRA WEST DIVISION, LIRA CITY: A CROSS-SECTIONAL STUDY. - Ojok Joel Rokko Rokko; Edmand Bakashaba (Student's Journal of Health Research, 2023)
Background. The study examined the relationship between parents' involvement and pupils' academic performance in Lira City.  Methodology A cross-sectional design was used and both the qualitative and quantitative techniques of collecting and analyzing data were exploited. Qualitative techniques were applied to the data collected using documentary review while quantitative techniques were applied to data collected using questionnaires. The study had a target population of 332 participants from which 178 respondents were selected using Kreijcie & Morgan's (1970) table of determining sample size.  Results The correlation between parents volunteering and the academic performance of pupils in the Lira West division was 0.321 with a sig value of 0.071. This indicated an insignificant relationship between parents volunteering and the academic performance of pupils in Lira City. The correlation between home environment and academic performance of pupils in primary schools was 0.563 with a sig value of 0.001. This indicated a significant positive relationship between the home environment and the academic performance of pupils in the Lira West division, Lira City. Therefore, the home environment for primary pupils influences their academic performance in Lira City.  The correlation between parents' care and the academic performance of pupils in primary schools was 0.741 with a sig value of 0.000. This indicated a significant positive relationship between parents' care and the academic performance of pupils in the Lira West division, Lira district.  Conclusion:  In conclusion, parents' care by providing fees and scholastic materials to primary pupils influences their academic performance Lira West division.  Recommendation: There should be sensitization of parents on their role in the academic performance of their children in primary schools within the Lira West division, Lira City.